Dialectic of Religion and Tradition: Investigating Remote Indigenous Communities Belief in Riau, Indonesia - Hasbullah Hasbullah; Suryan A. Jamrah; Riska Syafitri; Nur Aisyah Zulkifli (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2022)
Belief is the core of every religious teaching in advanced civilizations and remote indigenous communities. The existence and religious practice cannot be separated from the traditions that develop in the community. The interplay between religion and tradition is nearby. A qualitative approach was used to answer research questions related to (1) the relationship between religion and tradition in the Akit Tribe community and (2) to explain why this tradition is maintained. Data were obtained through in-depth interviews with informants like tribal chiefs, traditional healers, midwives, community leaders, and members. The results show that the practice of belief in the Akit Tribe follows their ancestors, even though they adhere to one official religion, especially Islam. Religion for the Akit Tribe is not crucial, it is only a compliment. Thus, there is no problem if they have a different religion. Religion is only for administrative purposes, such as getting married and making identity cards. Traditions are still maintained due to the low level of education and lack of understanding of their religion, especially Islam. It makes a practice of acculturation in belief and creates syncretism.